Analisis Aspek Akuntabilitas Pengelolaan Dana Haji Melalui Aplikasi SISKOHAT - Muhammad Nugraha Eka Wardana; Dwi Suhartini (Universitas Batanghari Jambi, 2023)
Based on data from the Hajj Financial Management Agency (BPKH), the total hajj funds up to December 2020 is 145.7 T rupiah. The amount of funds that are not small certainly requires good management by the Ministry of Religion. However, the facts on the ground are that corruption and funding of hajj funds are still going on, which has resulted in many people questioning the accountability of the management of these hajj funds. On the other hand, the Ministry of Religion is also trying to make improvements, one form of effort in bridging information to the public is maximizing the use of the Integrated Hajj Information and Computerization System (SISKOHAT). Through this research, we want to explore how the implementation and the impact caused by SISKOHAT will be. This study uses a qualitative method with a phenomenological approach to correlate the data obtained. This method is used to examine the condition of the problem of Hajj funds naturally and more deeply through various Hajj phenomena. Specifically, the research was conducted by collecting data along with observations. The research location is the Ministry of Religion of Blitar City, where the researchers chose this location because Blitar City is one of the